Tinjauan Yuridis Tindak Pidana Pencemaran Nama Baik Menurut KUHP dan UU ITE - Peni Anastasia Sitepu (Jurnal Hukum Lex Generalis, 2025)
This research focuses on defamation as a criminal offense under the Criminal Code and ITE Law. The purpose of this research is to determine the qualifications and law enforcement of criminal acts of defamation based on the Criminal Code and the ITE Law. This research uses normative juridical research, analytical research with a statutory approach. This research proves that the Criminal Code and ITE Law have the same qualifications regarding defamation, namely intentionally attacking a person's honor, self-esteem, reputation and good name with the aim of making it known to the public. The difference is that defamation in the Criminal Code is carried out directly by the perpetrator, whereas what is regulated in the ITE Law is carried out through electronic media by the perpetrator or parties who participate in the crime. Law enforcement of criminal acts of defamation is realized through prison sanctions and fines for perpetrators. The criminal sanctions contained in the ITE Law are more severe compared to the Criminal Code sanctions.